2009
DOI: 10.1007/s00894-009-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of red-shifting and blue-shifting hydrogen bonds occurring between imidazolidine derivatives and PEG/PVP polymers

Abstract: A theoretical study is presented with the aim to investigate the molecular properties of intermolecular complexes formed by the monomeric units of polyvinylpyrrolidone (PVP) or polyethyleneglycol (PEG) polymers and a set of four imidazolidine (hydantoine) derivatives. The substitution of the carbonyl groups for thiocarbonyl in the hydantoin scaffold was taken into account when analyzing the effect of the hydrogen bonds on imidazolidine derivatives. B3LYP/6-31G(d,p) calculations and topological integrations der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 56 publications
1
13
0
4
Order By: Relevance
“…A previous study with other imidazolidine-2,4-dione system (14) revealed that the following method is appropriate to elucidate the electronic aspects of the intermolecular interactions between the imidazolidine scaffold and the PVP and PEG polymers. The monomers were used instead of the polymers because of the intrinsic difficulty of taking into account all the degrees of freedom for the entire polymer in the quantum chemical calculations employed here.…”
Section: Molecular Modeling Of Fz4-polymer Interactionsmentioning
confidence: 99%
“…A previous study with other imidazolidine-2,4-dione system (14) revealed that the following method is appropriate to elucidate the electronic aspects of the intermolecular interactions between the imidazolidine scaffold and the PVP and PEG polymers. The monomers were used instead of the polymers because of the intrinsic difficulty of taking into account all the degrees of freedom for the entire polymer in the quantum chemical calculations employed here.…”
Section: Molecular Modeling Of Fz4-polymer Interactionsmentioning
confidence: 99%
“…1 Destas, é bem estabelecido pela cromodinâmica quântica que as interações fortes ocorrem entre prótons e nêutrons através da ação dos quarks e glúons, 2 cujo resultado é a formação do núcleo atômico denso e compacto. Presente em nível nuclear, as interações fracas são 10 13 menos intensas e são caracterizadas pelas manifestações dos bósons W (Weak nuclear force) e Z (Zero). 3 Interações eletromagnéticas são típicas de partículas elementares carregadas 4 e são 10 2 mais fracas em relação às interações fortes.…”
Section: Introductionunclassified
“…No cerne da química atômico--molecular, as interações consideradas fracas com características puramente eletrostáticas são as mais importantes, pois os sistemas são interpretados como sendo ligados 6,7 e não covalentes, 8,9 e nestas circunstâncias átomos formam as ligações químicas 10 e moléculas atingem condições eletrônicas propícias para formarem estruturas intermoleculares estáveis. 11 Na natureza há uma imensidade de sistemas estabilizados intermolecularmente, destes aqueles contendo regiões com altas densidades eletrônicas (pares de elétrons não compartilhados, [12][13][14] elétrons π, [15][16][17] ou hidretos [18][19][20][21] representados por Y -δ na ligação X-Y -δ ) são atraídos por espécies doadoras de prótons (ácidos de Lewis 22,23 simbolizados por H …”
Section: Introductionunclassified
“…34 Ligações de hidrogênio entre aminoácidos compõem as biomoléculas supramoleculares 35 formadas pela associação de diversas subunidades doadoras e receptoras de prótons estabilizadas cooperativamente pela ação de forças eletrostáticas, dispersivas, polares, repulsivas de spin ou transferências de carga. 36,37 Todavia, a cooperatividade supramolecular não é considerada uma propriedade intrínseca das macromoléculas, 38 uma vez que esta mesma fenomenalidade também se observa em estruturas medianas ou pequenas, os chamados agregados ou clusters. [39][40][41][42] Nestes sistemas, a estabilização é definida por um mecanismo de distribuição de energia denominado Não Aditividade (NA) ou Cooperatividade Eletrônica (CE), 43 em que as energias das ligações de hidrogênio são distribuídas de maneira uniforme entre as unidades doadoras (H−X) e receptoras (Y) de prótons.…”
Section: •••H E O•••h (Adenina•••timina E Citosina•••guanina)unclassified